Automated Bonding Analysis with Crystal Orbital Hamilton Populations. Issue 11 (28th June 2022) - George, Janine; Petretto, Guido; Naik, Aakash; Esters, Marco; Jackson, Adam J.; Nelson, Ryky; Dronskowski, Richard; Rignanese, Gian‐Marco; Hautier, Geoffroy
Abstract: Understanding crystalline structures based on their chemical bonding is growing in importance. In this context, chemical bonding can be studied with the Crystal Orbital Hamilton Population (COHP), allowing for quantifying interatomic bond strength. Here we present a new set of tools to automate the calculation of COHP and analyze the results. We use the program packages VASP and LOBSTER, and the Python packages atomate and pymatgen . The analysis produced by our tools includes plots, a textual description, and key data in a machine‐readable format. To illustrate those capabilities, we have selected simple test compounds (NaCl, GaN), the oxynitrides BaTaO2 N, CaTaO2 N, and SrTaO2 N, and the thermoelectric material Yb14 Mn1 Sb11 . We show correlations between bond strengths and stabilities in the oxynitrides and the influence of the Mn−Sb bonds on the magnetism in Yb14 Mn1 Sb11 . Our contribution enables high‐throughput bonding analysis and will facilitate the use of bonding information for machine learning studies. Abstract : Automated bonding analysis software has been developed based on Crystal Orbital Hamilton Populations to facilitate high‐throughput bonding analysis and machine‐learning of bonding features. This work presents the software and discusses its applications to simple and complex materials such as GaN, NaCl, the oxynitrides XTaO2 N ( X =Ca, Ba, Sr) and Yb14 Mn1 Sb11 .